Relación entre el gasto público y el saneamiento básico agua y desagüe en hogares de la Municipalidad Distrital de Urarinas 2018-2023 - Mestanza Gonzales, Luis Alberto (2025)
The research analyzes the relationship between public spending on sanitation in the District Municipality of Urarinas and access to water and sewage services during 2018-2023. Using a quantitative study with a non-experimental design and longitudinal data. This study seeks to enrich the body of knowledge on the effectiveness of municipal public spending on sanitation infrastructure in the context of a rural district. It was observed that the average public spending on sanitation was S/ 8,113,436, with an average interannual variation of 14.97%, and a fluctuating trend. The average access to water was 47.5%, access to sewage was 35% and the average combined access to water and sewage was 19.6%, this indicates that the district of Urarinas has great infrastructure challenges in sanitation for the coverage of these basic services to the population. On the other hand, the Spearman's Rho correlation coefficient of 16.5% is identified between the public expenditure on sanitation executed by the District Municipality and the level of access to the water and sewerage service. In addition, the significance level is 45.2%, which is not significant, therefore, it is concluded that a greater execution of public expenditure on sanitation by the District Municipality of Urarinas is not necessarily related to an increase in the level of access to the water and sewerage service in the homes of the district of Urarinas during the period 2018-2023.